Quantitative analysis of 0% infill density surface profile of printed part fabricated by personal FDM 3D printer - Alsoufi, Mohammad; Elsayed, Abdulrhman (International Journal of Engineering and Technology, 2018)
Fused deposition modeling or FDM technology is an additive manufacturing (AM) technology commonly used for prototyping applications which suffer seriously from low levels of fluctuated surface finish quality, demanding some hand ï¬nishing tool for even the necessary levels of 3D printed parts. This paper, therefore, aims at giving close attention to the variation in the surface roughness profile between the inner and the outer faces of FDM 3D printed parts based on advanced polylactic acid (PLA+) thermoplastic filament material. The surface roughness is quantitatively analyzed using a contact-type test-rig with a 90Â° angle measurement on each face along with each zone and sub-zone. The obtained results revealed that the surface finish of the inner faces is rougher than those of the outer faces as regards nozzle temperature, nozzle diameter, infill density and layer height is 220Â°C, 0.5 mm, 0% and 0.3 mm, respectively. The personal FDM 3D printer is thus confirmed to be an excellent platform, flexible, straightforward and cost-effective. Â